Sericea Lespedeza Control from Growing-Season Prescribed Burning Causes No Collateral Damage to Non-Target Species - J. A. Alexander; W. H. Fick; J. Lemmon; G. A. Gatson; K C Olson (Kansas Agricultural Experiment Station Research Reports, 2018)
Objective:The objective of this study was to evaluate the effects of 4 consecutive years of prescribed fire applied to native tallgrass range in either April, August, or September on forage biomass production, soil cover, and basal plant cover. Study Description:Nine fire-management units (14 ± 6 acres) were burned at 1 of 3 prescribed times: early spring (April 1), mid-summer (August 1), or late summer (September 1). Plant species composition and soil cover were assessed annually each July using a modified step-point technique. The Bottom Line:Burning during the summer for 4 consecutive years resulted in excellent control of sericea lespedeza, Baldwin’s ironweed, western ragweed, and invasive woody-stemmed plants, compared to traditional spring, dormant-season prescribed burning. In addition, major wildflower species prevalence increased in areas treated with prescribed fires during the summer compared with adjacent areas treated with prescribed fire during the spring.
Keywords: sericea lespedeza; prescribed burning; non-target species